An assessment of the regional innovation policy by the European Union based on bibliometrical analysis - Claudia Werker (Max Planck Institute of Economics, 2006)
The Lisbon strategy for growth and jobs seeks to use knowledge and innovation in the context of the European Research Area (ERA). To build the ERA the European Union (EU) implements - amongst others - regional innovation policy. Ample scientific publications have investigated how innovation drives regional dynamics. Therefore, we assess the goals of European regional innovation policy in the light of the scientific findings, which we collected and condensed by bibliometrical analysis. The general goals of the Lisbon strategy to at the same time stimulate growth and achieve cohesion of economic activities across the EU is not in line with the finding that positive cumulative and self-reinforcing processes go hand in hand with the agglomeration of economic activities. However, the goals of the specific innovation policies for the regional level are mainly in line with the scientific findings.
Keywords: O31; O33; O38; R11; 330; Region; innovation policy; European Union; bibliometrical analysis